The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.36953/ecj.021936-2175
|View full text |Cite
|
Sign up to set email alerts
|

Spatial mapping of groundwater quality using GIS for Jakham River basin of Southern Rajasthan

Abstract: The physico-chemical analysis of groundwater quality plays a significant role to manage the water resources for drinking as well as irrigation in the sub-humid and semi-arid agro-climatic areas. In this study, the hydrogeochemical analyses and spatial mapping of groundwater quality in the Jakham River Basin located in the southern part of Rajasthan were investigated.The groundwater quality samples were collected from 76 wells marked on the grid map of 5×5 km2 area.A spatial distribution in sampling location in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…Hence, the flow peaks brought by precipitation events arrive at the springs at different times, and the superposition effect of spring flow peaks and troughs leads to an overall small fluctuation of spring flow. Compared with the Jakham River basin 45 , Niangziguan karst area 2 , Heilongdong spring basin 46 , and other areas, the catchment area of the karst water in the study area is not large; therefore, the first reason has greater plausibility.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, the flow peaks brought by precipitation events arrive at the springs at different times, and the superposition effect of spring flow peaks and troughs leads to an overall small fluctuation of spring flow. Compared with the Jakham River basin 45 , Niangziguan karst area 2 , Heilongdong spring basin 46 , and other areas, the catchment area of the karst water in the study area is not large; therefore, the first reason has greater plausibility.…”
Section: Discussionmentioning
confidence: 90%
“…Geographical Extent: The study region encompasses the drainage area of the Kukadi River and its tributaries. Combination of the satellite imagery data and hydrogeological spatial analysis in geospatial environment is made easy to recognize and differentiate the drainage region (Gautam et al, 2021). According to Kang (2008), a flow direction raster shows the direction water which is flow out from each cell of a filled elevation raster.…”
Section: Study Regionmentioning
confidence: 99%
“…The tendency of occurrence of variation of groundwater level over time was monitored by (Gautam et al, 2022) at Jakham river basin of south Rajasthan in India, where statistical approach provided to monitor the water level during 2009-2019, it was concluded that groundwater level was found 15% decrease in trend during pre-Monsoon and very low percentage decrease was observed during post-Monsoon. Similarly ITA was applied by (Swain et al, 2022) in Jharkhand (India) to observe the uctuations of groundwater level, where it was concluded that ITA has precise tendency to generate the trend in shorter time series without restrictive assumptions, it evaluated the trends signi cantly at increasing rate for 17 sites during pre-Monsoon, and increasing trend at 14 sites during post-Monsoon period.…”
Section: Trend Of Groundwater Level Slope By Linear Regression Analysismentioning
confidence: 99%